Oil companies and governments; an account of the international oil industry in its political environment - Hartshorn, J. E. (London : Faber, 1962)
This book looks at the kaleidoscopic international circumstances of an industry in course of change.
"Published in the United States under the title Politics and world oil economics."
Includes index
Bibliography: p. 395-398.
asm; 21/01/19
Loans
Keywords: Petroleum industry and trade